Hydrogen embrittlement of ferrite-pearlite OCTG steels under electrochemical and gaseous hydrogen environment - Dong-Kyu Oh; Byoungchul Hwang (Journal of Materials Research and Technology)
This study investigates the hydrogen embrittlement behavior under electrochemical and gaseous hydrogen charging conditions, providing a multi-scale analysis of the correlation between fracture behavior and microstructural factors in ferrite-pearlite OCTG (oil country tubular goods) steel. The hydrogen embrittlement mechanism at the notch root was predominantly governed by the hydrogen-enhanced decohesion (HEDE) mechanism, which is facilitated by high triaxial stress states and hydrogen accumulation. Although the relative notch tensile strength (RNTS) value remained identical at 0.85 under a gaseous hydrogen pressure of 10 MPa and a current density of 0.5A/m2, the fracture behavior exhibited significant differences. Gaseous hydrogen charging facilitated deeper hydrogen penetration into the central regions, leading to quasi-cleavage fracture, whereas electrochemical charging predominantly induced brittle fracture near the surface. Thermal desorption analysis (TDA) revealed low-temperature peaks at 0.19 ppm and 0.07 ppm, corresponding to reversible trap site such as ferrite lattice defects and grain boundaries. A high-temperature peak of 0.40 ppm corresponded to hydrogen trapped in cementite, which was classified as an irreversible trapping site. Fractographic analysis revealed that ferrite underwent cleavage fracture due to hydrogen trapping at lattice sites, whereas pearlite exhibited shear cracking across the cementite lamellae, driven by localized stress concentration. These findings underscore the crucial role of microstructural characteristics and hydrogen trapping behavior in governing hydrogen embrittlement mechanisms, offering insights into the development of hydrogen-resistant OCTG steel.